Activity-based contracting for optimization of the mass distribution of insecticide-treated nets in the Democratic Republic of Congo: pilot implementation in Kwilu province - Losimba Likwela J; Kalonji Ntumba A; Ndolerire Isingoma C; Mukomena Sompwe E; Tsasa Mbuku E; Mbuse Angembo F; Mbuyu Lukunde E; Lukanu Ngwala P.; N.’siala Kumbi A; Panou I; Masoswa L; Mashako P; et al. (BMC Public Health, 2024)
Abstract Background Promoting the use of insecticide-treated mosquito nets (ITNs) is one of the main strategies for reducing malaria-related morbidity. An innovative activity-based contracting (ABC) approach has been implemented in Kwilu Province, Democratic Republic of Congo to optimize ITN mass distribution campaigns, with payments based on contractually defined programmatic outcomes for key campaign activities following independent verification of results. Methods This internal evaluation was carried out using a mixed methods approach combining qualitative and quantitative document and content analysis from a series of three workshops: validation workshops for campaign results at provincial level for the 2021 and 2022 campaigns; internal evaluation workshop for the Kwilu campaign as part of the ABC approach organized by “Santé pour tous en milieu rural” (SANRU) with its sub-contractors; and national campaign evaluation workshop organized by the National Malaria Control Program. Results The pilot campaign with the ABC approach in Kwilu has demonstrated better results than campaigns conducted using the standard, non-ABC, approach: better household coverage (99.9% vs. 97.3%) and improved compliance with ITN allocation to households based on the household size (98. 9% vs. 84.7%); lower loss of ITNs (0.3% vs. 0.5%) with immediate penalties for lost ITNs in the province under the ABC approach; shorter campaign lead times (14 vs. 28 weeks from the start of training to the launch of distribution). This last point is crucial, as it is likely to generate efficiencies and contribute to ensuring timely ITN replacement campaigns. Conclusion The challenges encountered and the lessons learned in the implementation of the pilot ABC approach in Kwilu could guide future distribution campaigns in the DRC and other African countries that would like to engage in distribution campaigns based on performance-based incentive contracts.